Analysis of the Stability of Bessel, Legendre and Euler Differential Equations - Muchammad Abrori (Jurnal Fourier, 2021)
The Bessel, Legendre and Euler differential equations discussed in this paper are second-level differential equations. These three equations become a system with two equations. The equilibrium point of all three of these equations is at the point (0,0). These three equations are locally asymptotically stable at the equilibrium point (0,0).